Associations between IL-6 and trajectories of depressive symptoms across the life course: Evidence from ALSPAC and UK Biobank cohorts - Amelia J. Edmondson-Stait; Ella Davyson; Xueyi Shen; Mark James Adams; Golam M. Khandaker; Veronique E. Miron; Andrew M. McIntosh; Stephen M. Lawrie; Alex S.F. Kwong; Heather C. Whalley (European Psychiatry)
Abstract